The Influence of Buddhism on the Traditional Rituals of the Buryats of the Eastern Sayan Region - D. M. Mansheev; G. P. Dondukova (Концепт: философия, религия, культура, 2024)
The article, based on field materials, examines the transformation of the worldview of the Buryats of the Eastern Sayan region under the influence of Buddhism. The relevance of the study comes from the need to clarify the value matrices of the traditional society of this region nowadays. The purpose of the study is to identify the key features of the interaction of traditional rituals with later beliefs among the bearers of these values. To achieve this goal, it was necessary to solve several problems: modern scientific ideas about the influence of Buddhism on traditional beliefs were systematized; the specific relationships of Buddhism, traditional shamanism and beliefs are highlighted; the dominant values of Buddhism reinterpreting the heritage of religious practices combined with it are clarified. Further, based on the analysis of field research, the most significant differences in the interpretations of such reinterpreted values were revealed, distinguishing them from traditional Buddhism. Using examples of existing customs, the modern development of the process of integration of the Buddhist worldview into the already existing ritual culture of the Sayan Buryats is traced. The research methodology includes comparative historical and religious studies and hermeneutical approaches. The field study used the method of interview. As a result, the role of Buddhism was confirmed as a way of adaptively rethinking the heritage of traditional culture in light of the modern crisis of values, associated, among other things, with the forgetting of traditions, consumer attitudes towards the environment, nature, society and even loved ones. Turning to Buddhism in the Eastern Sayan region today, as in the past, is becoming one of the ways to overcome such negative phenomena. Buddhism in the region not only absorbed beliefs that existed at different stages of the history of ethnic Buryatia, but also adapted them to its religious practice. A Buddhist worldview of this type corresponds to the concepts of vernacular religion accepted in modern religious studies. Forming a syncretical holistic picture of the world that corresponds to local conditions and the historical period, vernacular Buddhism defines a wide range of existing values that ideologically and practically incorporate the ritual culture that has developed over centuries.